ZnOCZnO sandwich structures: Fabrication and photocatalytic applications - Thi Ly Tran; Thi Le Na Vo; Hung-Anh Tran Vu; Quoc Viet Ho; Anh Tuan Duong; Viet Huong Nguyen; Huu Tuan Nguyen (MethodsX)
This study investigates the development of ZnOCZnO sandwich structures using ZnO thin films fabricated via the spatial atomic layer deposition (SALD) technique under atmospheric pressure. Carbon powders obtained from candle soot were introduced to modify the structural, optical, and photocatalytic properties of ZnO. The influence of this carbon layer on the structural, optical, and photocatalytic characteristics of the materials was comprehensively analyzed. The results indicate that incorporating carbon significantly enhances light absorption and charge carrier separation, leading to superior photocatalytic activity under UV light. The ZnOCZnO structures exhibited a reduced bandgap (3.20 eV) compared to bare ZnO (3.27 eV), facilitating improved photon absorption. X-ray diffraction (XRD) analysis revealed weaker and broader peaks in ZnOCZnO, suggesting reduced crystallite size and increased structural disorder due to carbon incorporation. The photocatalytic efficiency was assessed via methylene blue degradation under UV–Vis irradiation. The ZnOCZnO structures achieved an 88.2 % degradation rate after 180 min, surpassing the 62.9 % degradation observed for bare ZnO film. This enhancement is attributed to improved charge separation and suppressed recombination facilitated by the carbon interlayer. The findings highlight the potential of ZnOCZnO structures for environmental remediation and energy applications. • Development of ZnOCZnO sandwich structures using SALD under atmospheric conditions. • Integration of a candle soot-derived carbon layer to improve material properties. • Achieved enhanced photocatalytic efficiency through enhanced surface area and improved charge separation.